The Cartesian coordinate system as a unifying concept in school mathematics - Quiban, Ursula Cirujales- 1932- (1972)
The fundamental position occupied by the Cartesian coordinate system as a unifying concept in school mathematics was covered in this study. The major part was the display of opportunities or example by which the concept is used at different levels. In choosing the samples, stress is placed upon those which have the potentials in conveying other concepts. The four levels considered were : Kindergarten-simple act of concrete collection for comparison, then for pictorial representation; elementary level-making graphs of simple experiences in relations; secondary level-Cartesian coordinate is formally established, abstract ideas of relations are depicted through it by the graph of some functions; and the college level-intuitive work with advanced concepts.
"May 1972."
Vita.
Thesis (M.A.T. Mathematics)--University of the Philippines, Diliman.
Keywords: Mathematics -- Study and teaching -- Philippines; Coordinates